Local and global results for modified Szász–Mirakjan operators. (27th September 2016) - Gandhi, R.B.; ,; Mishra, Vishnu Narayan
Abstract : In this paper, we study a natural modification of Szász–Mirakjan operators. It is shown by discussing many important established results for Szász–Mirakjan operators. The results do hold for this modification as well, be they local in nature or global, be they qualitative or quantitative. It is also shown that this generalization is meaningful by means of examples and graphical representations. Copyright © 2016 John Wiley & Sons, Ltd.